The Influence of Work-Life Balance on Employee Performance with Perceived Organizational Support as a Moderating Variable - Faris, Muhammad; Rumijati, Aniek; Fitriasari, Fika (Universitas Muhammadiyah Malang, 2024)
This study examines the impact of work-life balance and perceived organizational support on employee performance at PT. Cahaya Fajar Kaltim. Using a quantitative approach with purposive sampling, 70 employees were selected as respondents. Data were analyzed through moderated regression analysis (MRA) using SPSS 25. The results show that both work-life balance and perceived organizational support significantly influence employee performance. Additionally, perceived organizational support acts as a moderating variable, strengthening the relationship between work-life balance and employee performance. Key findings include good work-life balance and perceived organizational support are associated with high employee performance, work-life balance has a significant positive effect on employee performance, and perceived organizational support enhances the effect of work-life balance on performance.